2014
DOI: 10.1097/ccm.0000000000000526
|View full text |Cite
|
Sign up to set email alerts
|

The Utility of Proadrenomedullin and Procalcitonin in Comparison to C-Reactive Protein as Predictors of Sepsis and Bloodstream Infections in Critically Ill Patients With Cancer*

Abstract: In critically ill patients with cancer, proadrenomedullin and procalcitonin both have a promising role in predicting bloodstream infections in a manner more helpful than C-reactive protein. These two biomarkers were superior to C-reactive protein in the prognostic analysis of response to antimicrobial therapy for those patients with documented infections. However, proadrenomedullin was superior to procalcitonin in predicting response in all febrile patients and was unique in showing increased levels among nonr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
30
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 34 publications
6
30
0
4
Order By: Relevance
“…ProADM has been used as a prognostic marker, either alone or in risk stratification with other hormonal propeptides in patients with sepsis and severe pneumonia (39). Importantly, ProADM has been shown to improve clinical pneumonia risk scores, and in a pilot intervention study, tended to decrease the length of stay without increased risk for readmissions by improving physicians’ admission and early discharge decisions (40). …”
Section: Clinical Chemistrymentioning
confidence: 99%
“…ProADM has been used as a prognostic marker, either alone or in risk stratification with other hormonal propeptides in patients with sepsis and severe pneumonia (39). Importantly, ProADM has been shown to improve clinical pneumonia risk scores, and in a pilot intervention study, tended to decrease the length of stay without increased risk for readmissions by improving physicians’ admission and early discharge decisions (40). …”
Section: Clinical Chemistrymentioning
confidence: 99%
“…The mortality increased with increasing plasma ADM level. The studies in the literature suggested that increased plasma ADM level in the intensive care unit patients with sepsis was superior to procalcitonin and CRP that reflect infection status of the patients and offer a more valuable tool in predicting mortality (8)(9)(10)(11). In a study that compared survivors and non-survivors, plasma ADM levels were found to be higher in non-survivors compared to survivors (15).…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies it was demonstrated that ADM level is superior to some other biomarkers, such as C-reactive protein (CRP), complete blood count (CBC), procalcitonin, pro brain natriuretic peptide (Pro BNP), acute physiology and chronic health evaluation II (APACHE II) score, in determining the mortality in sepsis (8)(9)(10)(11). Adrenomedullin is very highly expressed in adrenal gland in both zona glomerulosa and adrenal medulla, that's why we think that for elevation of plasma ADM level there should be adequate adrenal response (12,13).…”
Section: Adrenomedullin (Adm) Is a Peptide Initially Isolated From Phmentioning
confidence: 99%
“…It has further demonstrated the ability to distinguish sepsis from severe sepsis and septic shock, as well as predict mortality (Livaditi et al, 2006). Proadrenomedullin has also been of recent interest as a prognostic marker, correlating with sepsis severity and mortality (Akpinar, Rollas, Alagoz, Segmen, & Sipit, 2014;Debiane et al, 2014;Oncel et al, 2012;Suberviola et al, 2012).…”
Section: Sepsismentioning
confidence: 97%